2016
DOI: 10.31299/hrri.52.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Preschool teachers’ beliefs about their own competence in working with preschool children who show emotional and behavioral difficulties

Abstract: Cilj ovog rada bila je analiza samoprocijenjenih kompetencija odgojitelja za rad s djecom koja pokazuju emocionalne teškoće i probleme u ponašanju. U istraživanju su sudjelovala 82 odgojitelja predškolske djece. Podaci o samoprocjenjenoj kompetentnosti i samoefikasnosti odgojitelja u radu s djecom koja pokazuju emocionalne teškoće i probleme u ponašanju prikupljeni su putem upitnika koji je uključivao modificirane verzije upitnika Teacher´s Sense of Efficacy Scale (Tschannen-Moran i Woolfolk Hoy, 2001) i Teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Research has also shown that more knowledge for working with children with emotional difficulties and behavioural problems is gained through independent work and additional education (Valenčić Štembergar & Lepičnik Vodopivec, 2016). The research results point to the need for further improvement of preschool teachers to promote healthy child development and the prevention of risk behaviour and behavioural disorders in preschool children (Bašić, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has also shown that more knowledge for working with children with emotional difficulties and behavioural problems is gained through independent work and additional education (Valenčić Štembergar & Lepičnik Vodopivec, 2016). The research results point to the need for further improvement of preschool teachers to promote healthy child development and the prevention of risk behaviour and behavioural disorders in preschool children (Bašić, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The Teachers' Sense of Teacher Efficacy Scale (TSES), which was initially constructed and studied as the Ohio State Teacher Efficacy Scale (OSTES), was finally derived following several improvements and verifications (Gibson & Dembo, 1984;Tschannen-Moran et al, 1998;Tchannen-Moran & Hoy, 2001). As Tchannen- Moran & Hoy (2001) constructed the TSES to measure this construct, numerous authors validated its characteristics on different samples (Alcaraz-Ibsnez et al, 2018;Arata & Soto, 2012;Bakar & Mohamed, 2009;Bašić, 2008;Chang & Engelhard, 2016;Ekici & Güngör, 2014;Fabio & Palazzeschi, 2008;Fives & Buehl, 2009;Ghonsooly et al, 2014;Gurcay, 2015;Koomen et al, 2016;Lu & Manzar-Abbas, 2015;Maniadaki et al, 2006;Sariçoban, 2010;Ruan et al, 2015;Valenčić Štembergar & Lepičnik Vodopivec, 2016;Yada & Savolainen, 2017). According to various international studies, the TSES measures three constructs that are recognised as essential teacher competencies: efficacy in pupil engagement, efficacy in instructional strategies, and efficacy in classroom management.…”
Section: Introductionmentioning
confidence: 99%
“…Sudjelovanje u stručnom usavršavanju koje obrađuje teme poput osobitosti učenika s teškoćama, inkluziju, prilagodbe kurikuluma, upravljanje ponašanjem i asistivne tehnologije, pokazalo se povezanim s višim rezultatima samoefikasnosti za percipiranu sposobnost učitelja za rad s učenicima s teškoćama i u rezultatima istraživanja drugih autora (Brownell i Pajares, 1999;Buell i sur., 1999;prema Leyser i sur., 2011;Marković 2022). Može se utvrditi kako samoefikasnost korelira s procjenom vlastite kompetentnosti za obavljanje nekog posla jer na samoefikasnost učitelja snažno utječu individualni čimbenici poput vrijednosti, motivacije, samopouzdanja ili spremnosti za suočavanje s izazovima (Marković, 2022;Valenčić Štembergar i Lepičnik Vodopivec, 2016), dok su kompetencije temeljene na znanjima, sposobnostima, vještinama i stavovima, a i tu mogućnost otvaraju rezultati dobiveni provedenim istraživanjem.…”
Section: Zastupljenost Inkluzivnih Predmeta U Obrazovanju Budućih Uči...unclassified